DID THE BURNOUT LEVELS OF THE NURSES AFFECT THEIR PROFESSIONAL COMMITMENT DURING THE COVID-19 PANDEMIC PROCESS? - Serap Altuntaş; Fatoş Tozak (International Journal of Health Services Research and Policy)
This descriptive, cross-sectional, and correlational study investigated the effect of burnout on nurses' professional commitment during the COVID-19 pandemic. Nurses have been experiencing high levels of burnout since the onset of the COVID-19 pandemic. However, we know little about how burnout affects their professional commitment. The study was conducted between March 2021 and April 2021. The sample consisted of 671 nurses. Participation was voluntary. Data were collected online using a personal information form, the Maslach Burnout Inventory (MBI), and the Nursing Professional Commitment Scale (NPCS). The data were analyzed using the Statistical Package for Social Sciences (SPSS) at a significance level of 0.05. Half of the participants stated that the pandemic adversely affected their professional commitment (51.4%). More than a quarter of the participants noted that they considered quitting (36.4%). Participants had a mean MBI and NPCS score of 2.43±0.52 (above average) and 2.07±0.76 (average), respectively. Their MBI and NPCS scores were negatively correlated (r=-0.428; p=0.001). Burnout explained 18% of the total variance of professional commitment (p=0.000; R2: 0.182). Nurses experience high levels of emotional exhaustion and depersonalization during the pandemic, resulting in reduced professional commitment. There is also a positive correlation between personal accomplishment and professional commitment.